Reappearance of a Mistake. (On the history of a disappeard text by N.A. Nekrasov) - Alexander I. Feduta (Литературный факт, 2020)
In posthumous editions of K.I. Chukovsky’s works, including the newest 15-volume Collected Works, his article “The Poet and the Executioner” (1922), which is essentially devoted to the poem “Raising the Grace Cup...” addressed to M.N. Muravyov-Vilensky, is re-published. In the 1930s B.Ya. Bukhshtab finally disavowed the authorship of N.A. Nekrasov, and Chukovsky not only excluded this poem from the body of the poet's works, but also refused to republish his article. Now its republishing requires detailed reservations and explanations, which can be facilitated by the reconstruction of scientific polemics of the past decades. Thу article is devoted to its history.